Effect of Spacing and Fertilizer Levels on Flowering and Yield of Zucchini (Cucurbita pepo L.) - LATA, HEM; KHANDEKAR, R G; HALDAVANEKAR, P C; SALVI, V G; SALVI, B R (Journal of the Indian Society of Coastal Agricultural Research, 2017)
Zucchini (Cucurbita pepo L.) belongs to the family Cucurbitaceae and has been regarded as a highly polymorphic vegetable. A field research was conducted to study the effect of spacing and fertilizer levels on flowering and yield of zucchini. Trial was conducted in a split plot design with four spacing and three nitrogen levels. The parameters assessed were flowering and yield characters. Results showed that the interaction effects of spacing and nitrogen treatments had significant effect on flowering and yield traits. Highest number of female flowers (8.85), lowest sex ratio (15.33), highest number of fruits per plant (8.21), fruit yield per plant (3.86 kg), yield per plot (138.45 kg) and yield per hectare (74.78 t) was recorded in S (60cm x 60cm). Among the various nitrogen levels, treatment N (150 kg N ha ) produced maximum days to last harvest (68.05 days), highest number of fruits per plant (6.66), fruit yield per plant (3.19 kg), yield per plot (99.82 kg) and yield per hectare (53.9 t). Treatment combination S N (60 cm x 60 cm and 150 kg N ha ) produced significantly highest number of fruits per plant (8.26), fruit yield per plant (3.92 kg), yield per plot (139.94 kg) and yield per hectare (75.59 t). Based on the results of this study, it is recommended to apply 150 kg N ha and follow 60 cm x 60 cm spacing for getting highest production of Zucchini.